DISEMINASI PLATFORM MERDEKA MENGAJAR UNTUK GURU SMA NEGERI 6 KOTA SERANG - Sonny Rohimat; Sanusi Sanusi; Munthahanah Munthahanah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
The Minister of Education, Culture, Research and Technology launched the Merdeka Mengajar platform as an integral part of implementing the independent curriculum. The dissemination of the Merdeka Mengajar platform was carried out to welcome the new academic year, where SMA Negeri 6 Kota Serang was one of the schools that would implement an independent curriculum with independent choices to change. Principals and teachers in education units who will implement an independent curriculum with independent choices must take advantage of the teaching tools available on the Merdeka Mengajar platform. The dissemination activity was carried out in three steps, namely the presentation of the implementation of an independent curriculum with independent choices to change and a project to strengthen the profile of Pancasila students; presentation and discussion on the Merdeka Mengajar platform; and Follow Up Plans. In the presentation and discussion activities about the Merdeka Mengajar platform, the platform features and problems experienced by teachers in utilizing the platform were discussed. Dissemination of the Merdeka Mengajar platform is very important for teachers whose schools will implement an independent curriculum because on that platform various matters relating to the independent curriculum are provided.